2019
DOI: 10.2147/cmar.s195935
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy of complementary and integrative medicine on health-related quality of life in cancer patients: a systematic review and meta-analysis</p>

Abstract: Complementary and integrative medicine (CIM) has been used for improving health-related quality of life (HRQOL) in patients with cancer. The objective of this review is to evaluate the effects of CIMs on the HRQOL of cancer patients. We identified randomized controlled trials (RCTs) involving patients with cancer at any stage by retrieving electronic databases from the inception to February 14, 2018 (Systematic Review Registration: PROSPERO CRD42018091609). The main outcomes were HRQOL scores and related domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 69 publications
0
37
0
Order By: Relevance
“…Numerous studies have found that tai chi and qigong can have positive effects on the quality of life for a wide range of cancer patients [143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Numerous studies have found that tai chi and qigong can have positive effects on the quality of life for a wide range of cancer patients [143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162].…”
Section: Quality Of Lifementioning
confidence: 99%
“…However, there are some studies that suggest efficacy may be increased with supplement usage. Increased survival rates for colon, gastric, and lung cancer were demonstrated with use of Pan-Asian medicine (PAM) (66-68) CAM, including supplement use, was also associated with improved quality of life (46,69). Emotional distress, depression, insomnia, nausea, loss of appetite, and other symptoms as a result of disease or treatment can be addressed by CAM methods (see Table 1).…”
Section: Cam-drug Interactionsmentioning
confidence: 99%
“…So that, automatically, this event will encourage the advancement of science in the health sector for experts to carry out much integrated medical research to eradicate this pandemic coronavirus outbreak. 18,19 In the book of Fiqh, the thaharah chapter also explains the guidelines for purification in Islam. One of them is by doing ablution.…”
Section: Balance and Harmonization Of Human Body Systems Ala Thibbun mentioning
confidence: 99%